Investigating the relationship between posttraumatic Stress disorder (ptsd) symptoms and emotional intelligence among adolescent refugees from the Middle East - Ghazali, S.R (ASEAN Journal of Psychiatry, 2014)
Objective: The objective of this study was to establish the relationship between symptoms of PTSD and various scores of emotional intelligence scales. This study employed a cross-sectional research design. Participants were recruited from the local community health centre in Dearborn, Michigan, USA. The Child Posttraumatic Stress Reaction Index (CPTS-RI) measured the presence of PTSD symptoms and the Adolescents Multifactor Emotional Intelligence Scale (AMEIS) measured emotional intelligence. Results: The findings suggest an inverse relationship between PTSD severity and emotional intelligence. The PTSD score was negatively correlated with all AMEIS subscales. Two significant negative correlations were found in the tasks of using emotion and understanding emotion. Conclusion: Findings suggest that individuals with severe PTSD symptoms appear to lack the abilities to understand and use emotions. These findings might be useful in identifying factors that may contribute to decreasing the severity of PTSD symptoms of these children. Implications of the findings were discussed, and recommendations for future research are presented.